Mid- to lower-crustal architecture of the northern Lachlan and southern Thomson orogens: evidence from O–Hf isotopes. Issue 7 (17th November 2018) - Waltenberg, K.; Bodorkos, S.; Armstrong, R.; Fu, B.
Abstract: The nature of the substrate below the northern Lachlan Orogen and the southern Thomson Orogen is poorly understood. We investigate the nature of the mid- to lower-crust using O and Lu–Hf isotope analyses of zircons from magmatic rocks that intrude these regions, and focus on the 440–410 Ma time window to minimise temporal effects while focussing on spatial differences. Over the entire region, weighted mean δ 18 O values range from 5.5 to 9.8‰ (relative to VSMOW, Vienna Standard Mean Oceanic Water), and weighted mean ϵHft range from −8.8 to +8.5. In the northern Lachlan Orogen and much of the southern Thomson Orogen, magmatic rocks with unradiogenic ϵHft (∼−7 to −4) and elevated δ 18 O values (∼9 to 10‰) reflect a supracrustal source component that may be common to both orogens. Magmatic rocks intruding the Warratta Group in the western part of the Thomson Orogen also have unradiogenic ϵHft (∼−9 to −6) but more subdued δ 18 O values (∼7‰), indicating a distinct supracrustal source component in this region. Some regions record radiogenic ϵHf and mantle-like δ 18 O values, indicative of either a contribution from arc-derived rocks or a direct mantle input. In the northeast Lachlan Orogen Hermidale Terrane, magmatic rocks record mixing of the supracrustal source component with input from a infracrustal or mantle source component (ϵHft as high as +8.5, δ 18 O values as low as 5.5‰), possibly of Macquarie Arc affinity. Samples in the west-southwestern Thomson Orogen also record some evidence of radiogenic input (ϵHft as high as −0.5, δ 18 O values as low as 6.4‰), possibly from the Mount Wright Arc of the Koonenberry Belt. Overall, our results demonstrate a strong spatial control on isotopic compositions. We find no isotopic differences between the bulk of the Lachlan Orogen and the bulk of the Thomson Orogen, and some indication of similarities between the two.